AB0004 Erap1 Polymorphisms in Korean Patients with Behcet's Disease. (10th June 2014) - Kang, E.H.; Kim, S.; Kang, C.; Kang, Y.-M.; Kang, S.W.; Baek, H.J.; Lee, E.Y.; Lee, Y.J.; Lee, E.B.; Song, Y.W.
Abstract : Background: Non-synonymous ERAP1 single nucleotide polymorphisms (SNPs), rs10050860 and rs17482078, were found to be associated with Behcet's disease (BD) by a recessive model in Turkish patients [1]. Objectives: To investigate the association between ERAP1 SNPs and BD in Korean patients. Methods: DNA samples were obtained from 391 patients who met the International Study Group criteria for BD and from 800 age- and sex-matched healthy controls. Nineteen tag-SNPs (rs27980, rs27582, rs27038, rs149481, rs149173, rs27039, rs27043, rs42398, rs10050860, rs151928, rs13170045, rs27710, rs27529, rs25866, rs26652, rs26498, rs27045, rs10062964, rs28050) in and within 1kb from ERAP1 were selected for genotyping. Results: Allele-based analysis failed to detect any significant associations between 19 SNPs and BD after correction for multiple testing. In genotype-based analysis, only an intronic variant rs27043 was associated with BD by a dominant model (for AG+GG genotypes, 85.8% in patients vs. 72.4% in controls; OR [95% CI] =2.29 [1.65-3.20], p=6.2x10 –7, corrected p=1.18x10 -5 ). This association was significant in patients with uveitis (84.4% vs. 72.4%; OR [95% CI] =2.06 [1.28-3.29], p=0.002, corrected p=0.038) as well as in patients without uveitis (85.4% vs. 72.4%, OR [95% CI] =2.23 [1.46-3.41], p=0.0001, corrected p=0.0019) compared to controls. The non-synonymous rs10050860 found to be associated with BD in a Turkish GWAS did not show any statistical significance (minor allele frequencies of 4.7% in patients and 4.9% in controls). Conclusions: An intronic variant rs27043 was associated with BD notably by a dominant model in a Korean population. Efforts to impute genotypes using a reference panel from Korean/Asian HapMap data are underway to fully examine non-synonymous SNPs in strong linkage disequilibrium with rs27043 and their haplotype effects. References: Kirino Y, Bertsias G, Ishigatsubo Y, et al. Genome-wide association analysis identifies new susceptibility loci for Behçet's disease and epistasis between HLA-B*51 and ERAP1. Nat Genet 2013; 45: 202-7. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3438